Analisis Strategi Pemasaran dan Pengaruhnya Terhadap Kinerja Keuangan The Wood’s Coffee Tanjung Morawa - Fikaria Br Tarigan (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This study aims to analyze the marketing strategies implemented by The Wood's Coffee Tanjung Morawa and their impact on the company's financial performance. The main focus of this study is the marketing strategy through social media, which is increasingly becoming an effective tool in promoting products and increasing engagement with consumers. This study uses a qualitative approach with in-depth interview methods with marketing managers, social media staff, and several loyal customers. The results of the study indicate that the marketing strategy implemented through social media, including the use of Instagram and Facebook, has succeeded in increasing brand awareness and attracting new customers. In addition, the results of the financial analysis indicate that the implementation of an effective social media strategy has contributed significantly to increasing sales, which has led to an increase in the company's financial performance. However, the challenge of maintaining consistency and managing interactions on social media is an important factor for long-term success. This study provides insight into the importance of social media as an integral part of a marketing strategy to improve the company's financial performance.